The regulation of the COL5A1 gene via the 3' - UTR and its impact on Achilles Tendinopathy and other exercise-related phenotypes Yoonus Abrahams. - Abrahams, Yoonus (Department of Molecular and Cell Biology, 2014)
Includes abstract. Includes bibliographical references.